PENGGUNAAN MEDIA FLIPBOOK DALAM KEBERHASILAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI PESERTA DIDIK DI SD INPRES PANAIKANG II/I KOTA MAKASSAR - Faldi; Hafid, Erwin; Rusmin B, Muhammad; Nuryamin; Iqbal, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the role of using flipbook media in Islamic religious education learning at SD Inpres Panaikang II/I Makassar City, to describe the relevance of Islamic religious education learning and flipbook media in improving character at SD Inpres Panaikang II/I Makassar City, and to describe Islamic religious education learning based on flipbook teaching media at SD Inpres Panaikang II/I Makassar City. This type of research is qualitative which takes place in Panakkukang District, Makassar City. The data sources in this study are PAI teachers, students of SD Inpres Panaikang II/I Makassar City. The data collection methods used are observation, interview, and documentation methods. The research instruments are observation and interview guidelines with data analysis including data reduction, data presentation and drawing conclusions and verification. Data validity is carried out by data triangulation testing. The implication of the research is that SD Inpres Panaikang II/I Makassar City should add tools that support learning media so that the teaching and learning process so that learning objectives can be achieved, especially in Islamic religious education learning. The presence of Flipbook media is expected to have an important role in achieving teachers' goals in implementing good character attitudes to students at SD Inpres Panaikang II/I, Makassar City.